Transformation of Santri Identity in the Era of Globalization: A Systematic Literature Review of Cultural Hybridity, Digitalization, and Pesantren Resilience - Amalia Nasir; Tri Wahyudi Ramdhan; Mufaizin Mufaizin (al-Afkar, Journal For Islamic Studies, 2026)
Amidst the massive escalation of globalization and the phenomenon of digital disruption, the identity of santri (Islamic boarding school students) is undergoing a fundamental transformation from traditional-exclusive patterns toward a more dynamic, adaptive, and hybrid identity construction. This study aims to comprehensively map the dynamics of santri identity transformation using a Systematic Literature Review (SLR) of various reputable scientific literatures. By implementing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, 14 primary articles published between 2021 and 2026 were analyzed in-depth through qualitative synthesis techniques. The findings identify three main pillars of identity shift: (1) the internalization of information technology, such as the implementation of the Santri Identity Card (SIC) and the Pedatren management system, which have transformed into new instruments for data-based character discipline (digital behavioral control); (2) the emergence of a "hybrid identity" where santri are capable of negotiating religious values within secular public spheres and social media through glocalization strategies; and (3) the strengthening of structural resilience through the "Hybrid Leadership" model of Kyai, which integrates traditional charisma with modern participatory management. This research concludes that pesantren institutions have successfully executed a "Technology for Character" strategy, where modernity is adopted without degrading traditional roots. The results provide significant implications for the development of Islamic education policies in shaping the profile of the "New Santri" globally competitive individuals who remain firmly grounded in the principles of Islam Nusantara’s religious moderation.